The implementation of functional analysis using Value Analysis Value Engineering (VAVE) approach during New Product Development (NPD) phase - Ainul Farahin binti Abdullah (Kulliyyah of Engineering, International Islamic Universiti Malaysia, 2017)
To remain competitive in global marketplace, automotive manufacturing organizations need to improve their development process. One of the methods is by producing high-quality products that can meet customer desires and at the same time trying to increase the operating income requirements for the organizations. This is important to ensure the product can be properly developed with the right specification, quality, cost and time. Current intense worldwide competition in the global marketplace force these industries to generate better demanding environments which make them to think more than twice before applying their development guideline. This thesis attempts to develop a systematic approach that is able to measure and enhance the product value by either improving the product performance or decreasing the product cost through focusing on one of the tools used in Value Analysis Value Engineering (VAVE) methodology; Functional Analysis and its implementation during New Product Development (NPD) phase. A case study on product part problems from one of the automotive organisations in Malaysia is analysed, within several selected performance criteria's. Few concepts and designs within the scope model of this study are developed. The 2-Dimensional and 3-Dimensional simulation models are designed, tested and implemented using CATIA V6 simulation package to generate various development scenarios. The discrete simulation events are used to find the difference among the different concepts and designs. Then the performance measures of various development phases are used to produce and at the end introduce the alternative through the prototyping designs. The decision matrices are also developed in this thesis. The development of these matrices involved generation of several important tables. These matrices are capable of analysing the performance score of particular designs and showing the potential improvement. Furthermore, the application of these matrices also enable user to proceed with the cost evaluation before finally resolve the problems. The framework produce in this thesis is generated enough and may be used for further study either to test various development phases or extending its application to other problems.